2015
DOI: 10.1016/j.jnucmat.2014.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Fuel retention measurements in Alcator C-Mod using accelerator-based in situ materials surveillance

Abstract: This paper presents the first in-situ time-and space-resolved measurements of deuterium (D) fuel retention in plasma-facing component (PFC) surfaces using Acceleratorbased In-situ Materials Surveillance (AIMS) on the Alcator C-Mod tokamak. AIMS is a novel in-situ materials diagnostic technique based on the spectroscopic analysis of nuclear reaction products induced in PFC surfaces using an ∼MeV beam of deuterons from a compact linear accelerator in between plasma shots. AIMS measurements of D retention on inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In addition, the AIMS measurements indicate that the plasma does not deplete retained deuterium from the boron films over the course of a run day. This provides additional evidence that retention in boron films cannot sufficiently explain the net fuel retention observed on Alcator C-Mod, as there is insufficient atomic capacity for deuterium storage [70].…”
Section: Accelerator-based In-situ Materials Surveillancementioning
confidence: 83%
“…In addition, the AIMS measurements indicate that the plasma does not deplete retained deuterium from the boron films over the course of a run day. This provides additional evidence that retention in boron films cannot sufficiently explain the net fuel retention observed on Alcator C-Mod, as there is insufficient atomic capacity for deuterium storage [70].…”
Section: Accelerator-based In-situ Materials Surveillancementioning
confidence: 83%
“…54 Early results have proven the principle of the technique and shown that measurements could be routinely made between shots. [55][56][57] C. Divertor regimes and detachment physics Meeting the challenges of divertor power handling and erosion require better understanding of the underlying physics, through which improved designs and operating regimes can be achieved. The operating point of the divertor depends in large measure on the balance between parallel and perpendicular transport.…”
Section: à5mentioning
confidence: 99%
“…The latter involves chambers for in-situ experiments (e.g., exposure to plasma, implantation, thermal treatment) with simultaneous analyses to determine the dynamics of processes without breaking vacuum; the research challenges have been addressed in [45]. In-situ IBA, i.e., inside a fusion device, has been discussed for a long time and, once, it has been demonstrated in Alcator-C Mod [71]. However, such an approach in a reactor-class machine will not be possible.…”
Section: Discussionmentioning
confidence: 99%